2022
DOI: 10.1186/s42826-022-00117-4
|View full text |Cite
|
Sign up to set email alerts
|

Single injection of very mild dose botulinum toxin in the vastus lateralis improves testicular spermatogenesis and sperm motility in ageing experimental mice

Abstract: Background Botulinum toxin (BoNT) is a widely used therapeutic agent that blocks the excessive release of acetylcholine at the neuromuscular junction. Previously, repeated intracremasteric injections and slight overdose of BoNT have been reported to induce adverse effects in the testicular parameter of experimental rodents. However, a mild dose of BoNT is highly beneficial against skin ageing, neuromuscular deficits, overactive urinary bladder problems, testicular pain and erectile dysfunctions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…On the other hand, BPF-induced decline in AChE activities could be a result of oxidative stress 37 , 43 since hydroxyl radicals are involved in AChE inhibition 44 . The observed BPF-induced reduction in AChE will eventually leads to the accumulation of ACh which has also been shown to increase oxidative damage 45 , 46 . Furthermore, increase in ACh also inhibit GnRH secretion which in turn leads to a decrease in libido by impairing the activities of the HPG axis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BPF-induced decline in AChE activities could be a result of oxidative stress 37 , 43 since hydroxyl radicals are involved in AChE inhibition 44 . The observed BPF-induced reduction in AChE will eventually leads to the accumulation of ACh which has also been shown to increase oxidative damage 45 , 46 . Furthermore, increase in ACh also inhibit GnRH secretion which in turn leads to a decrease in libido by impairing the activities of the HPG axis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The direct effects of carbamates exposure to the testicular function, spermatogenesis, and sperm function, however, remains to be disclosed. Radhakrishnan et al reported that elevated concentrations of ACh induced oxidative stress in the testis, thus diminishing sperm motility [ 35 ]. This outcome was found, however, to be reverted by a mild intramuscular dose of Botulinum toxin in the inferior spermatic nerve plexus, a place known to regulate steroidogenesis [ 35 ].…”
Section: The Role Of Acetylcholine In Male Reproductive Functionmentioning
confidence: 99%
“…Radhakrishnan et al reported that elevated concentrations of ACh induced oxidative stress in the testis, thus diminishing sperm motility [ 35 ]. This outcome was found, however, to be reverted by a mild intramuscular dose of Botulinum toxin in the inferior spermatic nerve plexus, a place known to regulate steroidogenesis [ 35 ]. The Botulinum toxin acts through the cleavage of the SNARE proteins, preventing the release of ACh vesicles [ 36 ].…”
Section: The Role Of Acetylcholine In Male Reproductive Functionmentioning
confidence: 99%